The Validity of Integrated Islamic Ethnobotany Textbooks Based on the 3D PageFlip Application - Handayani, Isnaini Siwi; Ayatusa'adah, Ayatusa'adah; Lestariningsih, Nanik (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
Based on the analysis of needs, it is known that Ethnobotany learning in the Biology Tadris study program at IAIN Palangka Raya has not used integrated Islamic teaching materials, lecturers and students need integrated Islamic Ethnobotany textbooks that are valid for use in learning. This study aims to describe the validity of the integrated Islamic Ethnobotany textbook based on the 3D PageFlip. This research is part of development research with the ADDIE development model. This study uses a quantitative descriptive method for feasibility assessment based on the expert review (including two material expert validators, two media expert validators, and two interpreter expert validators) using a questionnaire. The results of the study indicate that the assessment of the material expert is 94.5% (very valid), the assessment of the media expert is 90% (very valid), and the assessment of the interpreter is 90% (very valid). Thus, textbooks can be declared very valid and suitable for use in learning.